Cement - Goldstein, Nechama (Israel, 2006)
Verzio FF Submission Portrait of a family living in a village in East Jerusalem, surrounded by the separation wall and trying to cope with the Israeli-Palestinian conflict. “Cement” is the story of a mother of 12 children who is unable to provide for them. It is a story of a family torn apart. “Cement” presents a reality in which children are forced to grow up too fast, some are forced to drop out of school and provide for the family while others are thrown into jail.